2020
DOI: 10.1002/smtd.202000090
|View full text |Cite
|
Sign up to set email alerts
|

The Promise of Nanopore Technology: Advances in the Discrimination of Protein Sequences and Chemical Modifications

Abstract: ever, only 21 000 distinct protein-coding genes were identified. [2] Meaning just a tiny percentage of DNA has the information necessary for translation of all the proteins present in human cells. Among these genes, only 150 are systematic targets of somatic cancer mutations 2850 are drivers of rare diseases when mutated and ≈1100 are involved in diseases caused by multiple genes. [3] We understand now that mutations are not the only factor responsible for human disease. Epigenetics, another factor of interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 85 publications
0
43
0
1
Order By: Relevance
“…Gaussian fits are used to determine the amplitudes of the blocked pore current and the most probable dwell time of the analyte, while the exponential fit is used to determine the mean interevent interval. For a detailed description of the processing of the collected data for nucleic acids and peptides, we refer the reader to references [114] and [115], respectively.…”
Section: Inherent Requirements Of the Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaussian fits are used to determine the amplitudes of the blocked pore current and the most probable dwell time of the analyte, while the exponential fit is used to determine the mean interevent interval. For a detailed description of the processing of the collected data for nucleic acids and peptides, we refer the reader to references [114] and [115], respectively.…”
Section: Inherent Requirements Of the Methodsmentioning
confidence: 99%
“…Furthermore, the time scale on which protein translocation occurs is too fast to resolve individual amino acids. Excellent and detailed reviews on challenges and advances in protein sequencing by nanopores can be found (see references [115,143,144]).…”
Section: Detection Of Proteins: Basic Requirementsmentioning
confidence: 99%
“…[ 6,7 ] Nanopore technology has been a proven success for DNA sequencing and is making its first strides toward protein sequencing. [ 8–12 ] Aiming to discuss challenges, opportunities, and applications for the nanopore field and encourage cross‐disciplinary collaboration, [ 13–16 ] the 2020 Nanopore Weekly Meeting took place online every Monday starting from October 19, 2020 as a continuing international event after the 2020 Nanopore Electrochemistry Meeting, which was transformed to an online event in the past October due to the COVID‐19 pandemic. The 2020 Nanopore Weekly Meeting was chaired by Professor Mathias Winterhalter from Jacobs University (Germany), Professor Meni Wanunu from Northeastern University (USA) and Professor Yi‐Tao Long from Nanjing University (China) (Figure 1).…”
Section: Figurementioning
confidence: 99%
“…For nucleic acids, techniques have been established to determine the sequence or specific structures of both DNA and RNA [13][14][15][16][17]. Besides, single molecule sensing of proteins is another promising application of nanopore technology [18]. Various nanopore proteins have been used for detection of peptides [19,20], protein biomarkers [21][22][23][24][25], post-translational modifications [26], protein unfolding [27], and protein conformation [28].…”
Section: Introductionmentioning
confidence: 99%